A experiência organizacional dos trabalhadores rurais no município do Crato - CE (1960 – 1970) - Silva, João Paulo Fernandes da (2010)
This research analyzes the process of organization of rural workers in Crato, in the State of Ceará, between 1960 and 1970: period in which the first nuclei of rural trade unions appeared in the micro region of Cariri. It is these trade unions that somehow make room for the claims of those men and women, nurturing and linking their experiences, and giving us a view of the peculiarities of their lives. The interpretations developed here follow a different approach from that of those who analyzed Cariri’s agrarian history. We based this work on a view that these social subjects would hardly organize themselves and define their own activities, and on the idea that they cannot be seen as a mere support for certain institutions like the Church, trade unions and political parties. Our interest is to understand how they formed and fashioned the basic elements of their socio-economic organization, and to comprehend the social relations of their work, whose nuances reflected directly in their lives.